Nose to brain strategy coupled to nano vesicular system for natural products delivery: Focus on synaptic plasticity in Alzheimer's disease - Nunzia Maisto; Dalila Mango (Journal of Pharmaceutical Analysis)
A wide number of natural molecules demonstrated neuroprotective effects on synaptic plasticity defects induced by amyloid-β (Aβ) in ex vivo and in vivo Alzheimer's disease (AD) models, suggesting a possible use in the treatment of this neurodegenerative disorder. However, several compounds, administered parenterally and orally, are unable to reach the brain due to the presence of the blood-brain barrier (BBB) which prevents the passage of external substances, such as proteins, peptides, or phytocompounds, representing a limit to the development of treatment for neurodegenerative diseases, such as AD. The combination of nano vesicular systems, as colloidal systems, and nose to brain (NtB) delivery depicts a new nanotechnological strategy to overtake this limit and to develop new treatment approaches for brain diseases, including the use of natural molecules in combination therapy for AD. Herein, we will provide an updated overview, examining the literature of the last 20 years and using specific keywords that provide evidence on natural products with the ability to restore synaptic plasticity alterations in AD models, and the possible application using safe and non-invasive strategies focusing on nano vesicular systems for NtB delivery.